Storm signals: structural adjustment and development alternatives in the Caribbean - McAfee, Kathy (Zed Books LondonGB, 1991)
Examines the conflict between the divergent perspectives of the Caribbean Basin Initiative, USAID and structural adjustment on the one hand and the holistic Caribbean-centered development alternatives created by local non-governmental organizations on the other hand. Pinpoints the policies that threaten to block the promising initiatives of the region's popular movements and proposes constructive policy alternatives.